Lipstick as a Female Student’s Visual Communication Strategy - Dhuha Hadiyansyah; Era Bawarti; Maria Ulfa (Journal of English as A Foreign Language Teaching and Research, 2024)
Symbolism through coloring is commonly used in various social communications because color is significant for representing ideas, feelings, emotions, beliefs, and spirituality. Color gives character to objects and aboutness, including the color of lipstick on someone’s lips. This descriptive-qualitative study using in-depth interviews explored how female students at the Al-Azhar University of Indonesia (UAI) represented certain meanings through their choice of lipstick colors. This study was conducted objectively and avoided gender bias. The research found that even though they semiotically did not know the associative or connotative meaning of certain colors, the informants admitted to using lipstick for various reasons, namely, for the face to look bright and fresh, being more confident and prettier, showing their natural beauty, and displaying a cheerful impression. However, the analysis proved that after taking a closer look at the 10 lipstick color choices that have been reviewed, the subconscious message they want to convey is quite complex, ranging from optimism, cheerfulness, joy, modesty, warmth, wanting to be the center of attention, femininity, passion and love, and sensuality.